Preliminary Analysis to the Visual Identities of Bandung Creative Industries during Pandemic (2019-2023): Case study of Monoponik Studio, Pikir Mikir Studio, and Dassein Design Bureau - Supriadi, Olivine Alifaprilina; Eka Nastiti, Nisa; Kusuma Ayu, Intan (Telkom University, 2024)
This study examines the development of visual identity in Bandung's creative industry during the COVID-19 pandemic (2019–2023), focusing on the portfolios of Monoponik Studio, Pikir Mikir Studio, and Dassein Design Bureau. Using a qualitative approach, the research analyzes key visual identity elements—logotype, symbol, color, and typeface—to highlight design trends and their adaptation to pandemic-driven challenges. Findings reveal a shift toward minimalist styles, high-contrast colors, and designs optimized for digital and print platforms, with the food and beverage sector being the most active. Emotional resonance, scalability, and local branding emerged as crucial strategies during this period. This study differs from previous ones in that it examines real-world examples from design studios in Bandung during the COVID-19 pandemic. By focusing on this time and place, it shows how visual identity changed in response to real-world challenges. This makes the study useful for designers and researchers who want to understand how design adapts during difficult times.